Far North-East of Russia in Lexicographic Description - O. E. Shepileva (Научный диалог)
The article is devoted to G. V. Zotov’s Dictionary of Regional Lexis of the Far North-East of Russia. The relevance of study is determined by the need to study the linguistic facts of dialect and regional character. The novelty of research is seen in the fact that earlier G. V. Zotov’s Dictionary of Regional Lexis of the Far North-East of Russia has not become the object of special linguistic description. The paper provides an overview of the main studies related to the study of Russian speech in the Far North-East of Russia in the 18th - first half of the 20th century. Attention is paid to the history of creation and publication of the dictionary. The questions related to the structure of the dictionary, the construction of the dictionary article, special lexicographic marks, presentation of illustrative material are considered. Special attention is paid to the glossary representing the centuries-old complex of knowledge and ideas of the Russian old-resident population of the North-Eastern regions of Russia. The classification of the main lexical-thematic groups of units fixed in the dictionary is proposed. On the example of fishing terms it is proved that the fragment of the language picture of the world reflects the features of the Russian old-resident population in this territory. The author raises the question of functioning of borrowings from the languages of indigenous population of the Far North-East of Russia, testifying to the various contacts of the alien Russian and autochthonous population. The article provides examples of dictionary definitions, justifies the value of the lexicographical source.